Vaccination and serological status for hepatitis B in Family Health care Professionals - Oliveira, Valéria Conceição de; Guimarães, Eliete Albano de Azevedo; Souza, Débora Aparecida Silva; Ricardo, Renata Aparecida (Rev Rene, 2011)
The main goal of this study is to describe the vaccination status and performance of serology in health professionals. The descriptive epidemiological study was carried in 15 Family Health Groups in Divinópolis (MG, Brazil) in 2010. The methodology provided the application of 108 questionnaires to health professionals. Among the 108 surveyed, 89.4% were vaccinated with the three-dose regimen of the vaccine against hepatitis B. Moreover, it was detected that 81% of the workers did not undergo serological testing; 54.7% have contact with cutting tools, and 60.4% of them had never conducted training on biosafety. The results indicate high vaccination coverage against hepatitis B and a poor adherence to serology. So, the monitoring of vaccination status and the accomplishment of serological monitoring among health professionals is essential to ensure immunity to the disease.